2012
DOI: 10.1186/1472-6882-12-97
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the treatment of tinnitus: a systematic review of randomized clinical trials

Abstract: BackgroundComplementary and alternative medicine (CAM) has frequently been used to treat tinnitus, and acupuncture is a particularly popular option. The objective of this review was to assess the evidence concerning the effectiveness of acupuncture as a treatment for tinnitus.MethodsFourteen databases were searched from the dates of their creation to July 4th, 2012. Randomized clinical trials (RCTs) were included if acupuncture was used as the sole treatment. The Cochrane risk of bias tool was used to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 32 publications
3
69
1
4
Order By: Relevance
“…229,230 A systematic review in 2012 on acupuncture for the treatment of tinnitus included 9 RCTs, with a total of 431 participants. 222 Five of the RCTs used manual acupuncture (MA), [231][232][233][234][235] 1 used electroacupuncture (EA), 236 1 used both MA and EA, 237 and the other 2 used scalp acupuncture. 238,239 Five RCTs compared effectiveness of manual or electroacupuncture with sham acupuncture and showed no statistically significant improvement.…”
Section: Supporting Textmentioning
confidence: 99%
“…229,230 A systematic review in 2012 on acupuncture for the treatment of tinnitus included 9 RCTs, with a total of 431 participants. 222 Five of the RCTs used manual acupuncture (MA), [231][232][233][234][235] 1 used electroacupuncture (EA), 236 1 used both MA and EA, 237 and the other 2 used scalp acupuncture. 238,239 Five RCTs compared effectiveness of manual or electroacupuncture with sham acupuncture and showed no statistically significant improvement.…”
Section: Supporting Textmentioning
confidence: 99%
“…Acupuncture: We have found no published studies showing the bene it or ef icacy of acupuncture in the treatment of tinnitus [21].…”
Section: Treatment Strategies For Tinnitusmentioning
confidence: 99%
“…A systematic review found nine randomised controlled trials (RCTs; mostly poor quality) of acupuncture for tinnitus 8. Five (n=167; data not pooled) compared acupuncture or electroacupuncture with sham-acupuncture and found no benefit (e.g.…”
Section: Non-drug Treatmentmentioning
confidence: 99%
“…Five (n=167; data not pooled) compared acupuncture or electroacupuncture with sham-acupuncture and found no benefit (e.g. mean difference in THI 0.5, 95% CI –14.1 to +15.1) 8. Two compared one-time scalp acupuncture with penetrating sham acupuncture at non-acupoints; in one (n=76), more patients having acupuncture achieved subjective symptom relief on a visual analogue scale (VAS; mean difference –1.34, p=0.02); the other (n=38) found no difference on otoacoustic emission amplitude.…”
Section: Non-drug Treatmentmentioning
confidence: 99%